David Mitrany on the international anarchy. A lost work of classical realism?. (October 2017) - Ashworth, Lucian M
Although David Mitrany's international thought is not usually associated with the concept of the international anarchy, I argue that his analysis actually compares two forms of anarchical order. The first form is the order associated with the relations between states, while the second is his functional alternative to this order. The functional approach is anarchical in the sense that it remains an order without an orderer. In first analysing the dynamics and failings of the inter-state order, and then suggesting pragmatic process-orientated solutions to those failings, I argue that Mitrany follows a similar approach to his classical realist contemporaries.